Kebijakan Moneter: Peran Bank Sentral Dalam Mengendalikan Inflasi - Rini Puji Astuti; Shinta Amelia Putri; Ahmad Samsudin (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
Inflation, or the general rise in prices, is a big problem that can really hurt a country's economy. For Indonesia, a developing nation, keeping inflation under control is super important for steady economic growth and helping people get out of poverty. This study looks closely at how Bank Indonesia (our central bank) uses its policies to keep inflation in check and make sure our currency, the Rupiah, stays stable. We also explore how inflation affects Islamic banking, where fair and clear transactions depend on a stable currency. To do this research, we used a "literature review" method, which means we carefully read and analyzed many relevant books, journals, and reports. Our findings show that the central bank plays a vital role in fighting inflation by using tools like setting interest rates, buying and selling government securities (open market operations), and telling banks how much money they need to keep as reserves. The success of these policies depends on how much people trust the central bank, what's happening with the economy both locally and globally, and how well the central bank works with the government's financial policies. Basically, this research helps us better understand how our central bank keeps our money stable and helps our economy grow.